Automated Regression Testing and Data Analytics using Python - Dinesh Divsekar, Pravisha; Porob, Rupesh; Kuwelkar, Prof. Sonia (2019 4th International Conference on Recent Trends on Electronics, Information, Communication & Technology (RTEICT), 2019)
Testing is of utmost importance in industrial domain. Product testing makes sure that, software performs the dedicated task error free. Product testing is the key prerequisite before releasing the product. In order to satisfy the customer's requirements, it is essential to experiment the device against different test conditions. The key idea behind performing regression testing is to check for any recent script changes have not adversely affected the existing functionalities of the device. Data analytics using python is performed to draw necessary conclusions based on the type of test conducted. The aim of this paper is to perform automated regression testing and reusing the existing scripts with new modifications. Data analytics is being carried out on error data to visualize accuracy, deviations and other parameters.